Protective mental health factors in children of parents with alcohol and drug use disorders: A systematic review. - Olga Wlodarczyk; Mirjam Schwarze; Hans-Jürgen Rumpf; Franka Metzner; Silke Pawils (PLoS ONE)
Children of parents with drug and alcohol use disorders often grow up under severe stress and are at greater risk of developing psychological and social problems. However, a substantial proportion of affected children adapt to their distressing life conditions and show positive development in terms of their mental health. These children are described as resilient. One difference between resilient and maladapted children is the presence of protective factors. The aim of this systematic review is to provide an overview of the current state of the research concerning protective mental health factors in children of parents with alcohol or drug use disorders (COPAD). For that purpose, the PsychInfo, PubMed, CINAHL and ISI Web of Science databases were searched through January 2017. All the identified publications were screened using previously developed inclusion criteria. The search yielded 3,402 articles. Eleven of these publications (2003-2013) met the criteria for inclusion in the present review. Information on the studies was extracted using an extraction form. A narrative analysis was performed, and the methodological quality was examined using a checklist based on the Mixed Methods Appraisal Tool. The research identified familial, parental, child-related and biological factors that influenced mental health outcomes in affected children (N = 1,376, age range = 1-20 years). Overall, protective mental health factors are understudied in this target group. Most of the included studies were conducted in the United States and employed a cross-sectional design. A comparison of the included cross-sectional and longitudinal studies indicated consistent results related to a secure parent-child attachment. Based on the current state of the research, no causal conclusions with regard to the effectiveness of protective factors can be drawn. To develop effective prevention programs, further longitudinal studies and studies assessing the interactions between risk and protective factors are needed.